2009
DOI: 10.1086/597095
|View full text |Cite
|
Sign up to set email alerts
|

HIV Preexposure Prophylaxis in the United States: Impact on Lifetime Infection Risk, Clinical Outcomes, and Cost‐Effectiveness

Abstract: Background The combination of tenofovir and emtricitabine (TDF/FTC) shows promise as HIV pre-exposure prophylaxis (PrEP). We sought to forecast clinical, epidemiologic, and economic outcomes of PrEP, taking into account uncertainties regarding efficacy, risk of resistance and toxicity, behavioral disinhibition, and drug costs. Methods We adapted a computer simulation of HIV acquisition, detection, and care to model PrEP in high-risk (1.6% average annual HIV incidence) men who have sex with men (MSM) in the U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
207
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 241 publications
(218 citation statements)
references
References 42 publications
6
207
2
1
Order By: Relevance
“…A 2008 study of pre-exposure prophylaxis by Desai and colleagues [50] calculated that the incremental cost per QALY gained in the US was $31,970 (2007 US$), while a year later Paltiel and colleagues [51] calculated that the incremental cost per QALY saved was $298,000 (2006 US$). Both of these studies used HIV transmission and progression models to estimate the cost of reducing the number of new HIV infections, and both used published estimates of the cost of HIV treatment to generate their estimates of the incremental cost of a QALY.…”
Section: Cost-effectiveness Studies Of Pre-exposure Prophylaxismentioning
confidence: 99%
“…A 2008 study of pre-exposure prophylaxis by Desai and colleagues [50] calculated that the incremental cost per QALY gained in the US was $31,970 (2007 US$), while a year later Paltiel and colleagues [51] calculated that the incremental cost per QALY saved was $298,000 (2006 US$). Both of these studies used HIV transmission and progression models to estimate the cost of reducing the number of new HIV infections, and both used published estimates of the cost of HIV treatment to generate their estimates of the incremental cost of a QALY.…”
Section: Cost-effectiveness Studies Of Pre-exposure Prophylaxismentioning
confidence: 99%
“…Par exemple, proposer la PrEP à 60 % des HSH pourrait réduire de 30 à 55 % le nombre de nouvelles infections au cours des dix prochaines années si la PrEP s'avérait efficace à 40-90 % [39]. Cibler une population jeune, et/ou où l'incidence du VIH est plus élevée, et/ou où l'usage du préservatif est faible, et/ou où le taux de dépistage des personnes VIH + reste faible contribuerait à augmenter le rapport coût/efficacité [40]. En effet, l'implémentation de la PrEP dans une population où le taux de dépistage est faible, et donc la proportion de …”
Section: Impact De La Prep Au Niveau Populationnelunclassified
“…Despite the indications of biologic effectiveness, the implementation of PrEP will need to overcome many challenges to provide a meaningful benefit at the population level. Mathematical models have suggested that the effectiveness of PrEP may be offset by low uptake, suboptimal adherence, and risk compensation, which refers to increases in HIVrisk behavior among PrEP users on the assumption that they are protected against HIV infection (Abbas et al 2007;Desai et al 2008;Paltiel et al 2009). As was the case during the implementation of ARV for treating HIV infections, plans for PrEP implementation will likely include multiple components on optimal drug delivery, safety screening, behavioral intervention, integration of PrEP as part of comprehensive care, and monitoring the impact of PrEP at the population level (Underhill et al 2011).…”
Section: Future Directions and Challengesmentioning
confidence: 99%